Effects of different weights and lifting postures on balance control following repetitive lifting tasks in construction workers. Issue 3 (10th July 2017) - Antwi-Afari, Maxwell Fordjour; Li, Heng; Edwards, David John; Pärn, Erika Anneli; Seo, JoonOh; Wong, Arnold
Abstract : Purpose: Repetitive lifting tasks have detrimental effects upon balance control and may contribute toward fall injuries, yet despite this causal linkage, risk factors involved remain elusive. The purpose of this paper is to evaluate the effects of different weights and lifting postures on balance control using simulated repetitive lifting tasks. Design/methodology/approach: In total, 20 healthy male participants underwent balance control assessments before and immediately after a fatiguing repetitive lifting tasks using three different weights in a stoop (ten participants) or a squat (ten participants) lifting posture. Balance control assessments required participants to stand still on a force plate with or without a foam (which simulated an unstable surface) while center of pressure (CoP) displacement parameters on the force plate was measured. Findings: Results reveal that: increased weight (but not lifting posture) significantly increases CoP parameters; stoop and squat lifting postures performed until subjective fatigue induce a similar increase in CoP parameters; and fatigue adversely effected the participant's balance control on an unstable surface vis-à-vis a stable surface. Findings suggest that repetitive lifting of heavier weights would significantly jeopardize individuals' balance control on unstable supporting surfaces, which may heighten the risk of falls. Originality/value: This research offers an entirely new and novel approach to measuring the impact that different lifting weights and postures may have upon worker stability and consequential fall incidents that may arise.